TEACHERS' STRATEGIES IN OVERCOMING LEARNING DIFFICULTIES OF AL-QUR'AN IN DYSLEXIC STUDENTS - Salma Rozana; Rafika Nisa; Suhana Sarkawi; Al-Amin (International Journal of Teaching and Learning, 2024)
Dyslexia is a specific learning disorder known for difficulties in the acquisition of reading skills, especiall y in terms of reading speed and fluency as well as text comprehension. The disorder is neurological in nature and often genetic, with affected individuals having difficulties in word recognition, decoding language sounds, and processing and recalling visual and verbal information. Although dyslexia is not related to general intelligence levels, it can affect various aspects of learning and oral and written communication. The study in this research uses the literature research method. The results show that Teachers can overcome the difficulty of learning the Qur'an in dyslexic students by applying multisensory strategies, which involve the use of various senses in the learning process. These strategies include visualization of letters and words, auditory through repeated recitations, and kinesthetic such as writing and arranging letters. It is also important for the teacher to provide motivation and emotional support, as well as modify the pace of learning according to the individual needs of the student, thus creating a pleasant learning environment and minimizing frustration. This personalized approach increases students' confidence in learning the Qur'an and makes it easier for them to overcome the barriers caused by dyslexia.